Marketing Mix Factors Influencing Consumers Purchasing Decision for thePan Products in Bangkok - รัศมีโชติ บุญสม; พูลสวัสดิ์ กิตติพร; ถนอมเวช ปริษฐา; พรหมมา พิสุทธิ์; วชิรวรกุลชัย วรวุฒิ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to examine: 1) The importance level of the marketing mix factors of Pan brand products among consumers in Bangkok; 2) the level of consumer opinions regarding the decision-making process in purchasing Pan brand products; and 3) the factors influencing consumers’ purchase decisions for Pan brand products in Bangkok. The sample consisted of 400 consumers who had purchased Pan brand products in the Bangkok area. A questionnaire was used as the research instrument, and the data were analyzed using Mean, Standard Deviation, and Multiple Regression Analysis. The results revealed that: 1) the overall importance level of the marketing mix factors of Pan brand products among consumers in Bangkok was at a high level. When considered by dimension, the factor with the highest level of importance was product, followed by process, physical evidence, people, price, place, and promotion, respectively. 2) The overall level of consumer opinions regarding the purchase decision-making process was also high. The highest-ranked dimension was information search, followed by purchase decision, evaluation of alternatives, post-purchase behavior, and need recognition, respectively. 3) The regression analysis indicated that product and promotion factors significantly influenced consumers’ purchase decisions for Pan brand products in Bangkok at the 0.05 level, with coefficients the multiple correlation coefficient (R) was 0.783, and the coefficient of determination (R²) indicated a total predictive power of 60.50%.